Cold Dark Matter Cosmology Conflicts with Fluid Mechanics and Observations - Carl H. Gibson (Journal of Applied Fluid Mechanics, 2008)
Cold dark matter (CDM) cosmology based on the Jeans 1902 criterion for gravitational instability gives predictions about the early universe contrary to fluid mechanics and observations. Jeans neglected viscosity, diffusivity, and turbulence: factors that determine gravitational structure formation and contradict small structures (CDM halos) forming from non-baryonic dark matter particle candidates. From hydro-gravitational-dynamics (HGD) cosmology, viscous-gravitational fragmentation produced supercluster (10^46 kg), cluster, and galaxy-mass (10^42 kg) clouds in the primordial plasma with the large fossil density turbulence (3 ×10 ^ -17 kg m ^ -3 ) of the first fragmentation at 10^12 s, and a protogalaxy linear morphology reflecting maximum stretching on vortex lines of the plasma turbulence at plasma-gas transition at 10^13 s. Gas protogalaxies fragmented into proto-globular-star-cluster mass (10 ^36 kg) clumps of protoplanet gas clouds that are now frozen as earth-mass (10^ 24-25 kg) Jovian planets of the baryonic dark matter, about 30,000,000 rogue planets per star. Observations contradict the prediction of CDM hierarchical clustering cosmology that massive Population III first stars at 10^16 s existed but support the HGD prediction of gentle formation of small first stars in globular-star-clusters soon after 10^13 s.